Human Centered Interactive Animated Video to Enhance Primary Students' Learning Enthusiasm in Human Digestive System Instruction: A Classroom Action Study in an Indonesian Islamic Elementary School - Fitria Fathkul Khotimah; Tabroni; Pauzan Azim (WISE Pendidikan Indonesia, 2026)
Elementary science teachers need digital media that are not only visually attractive but also instructionally meaningful for young learners who often struggle with abstract biological processes. This classroom action study examined how an interactive animated video could improve fifth-grade students' learning enthusiasm in human digestive system instruction at an Indonesian Islamic elementary school. The study involved 21 students and was implemented through two action cycles consisting of planning, action, observation, and reflection. Data were collected through student enthusiasm questionnaires, classroom observation sheets, teacher implementation observation, interviews, and documentation. The intervention used a short animated video showing the digestive pathway from the mouth to the anus, embedded with guiding questions, student worksheets, and group discussion. The findings show a consistent improvement in learning enthusiasm. The questionnaire mean increased from 2.26 in the pre-cycle to 3.00 in Cycle I and 3.39 after Cycle II, while classroom observation scores increased from 2.00 to 3.00 and then to 4.00. Students became more attentive, more willing to ask and answer questions, and more positive toward science learning. These results suggest that interactive animated video, when combined with teacher facilitation and reflective classroom improvement, can create a more engaging, enjoyable, and student-centered elementary science learning environment.